2013
DOI: 10.1017/jfm.2013.603
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of transitional flow in a toroidal pipe

Abstract: The flow instability and further transition to turbulence in a toroidal pipe (torus) with curvature (tube-to-coiling diameter) 0.049 is investigated experimentally. The flow inside the toroidal pipe is driven by a steel sphere fitted to the inner pipe diameter. The sphere is moved with constant azimuthal velocity from outside the torus by a moving magnet. The experiment is designed to investigate curved pipe flow by optical measurement techniques. Using stereoscopic particle image velocimetry, laser Doppler ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 35 publications
(62 reference statements)
10
27
1
Order By: Relevance
“…All curvatures in the grid revealed spectra with unstable eigenvalues for Re < 6 × 10 3 . This result confirms the numerical observations by Di Piazza & Ciofalo (2011) as well as the experiments by Kühnen et al (2014Kühnen et al ( , 2015 and extends these studies, which are limited to the low curvature range. Most importantly, it proves that this flow is linearly unstable, in obvious contrast to the flow inside a straight pipe (see Schmid & Henningson (1994) and citations therein).…”
Section: Stability Analysissupporting
confidence: 92%
See 1 more Smart Citation
“…All curvatures in the grid revealed spectra with unstable eigenvalues for Re < 6 × 10 3 . This result confirms the numerical observations by Di Piazza & Ciofalo (2011) as well as the experiments by Kühnen et al (2014Kühnen et al ( , 2015 and extends these studies, which are limited to the low curvature range. Most importantly, it proves that this flow is linearly unstable, in obvious contrast to the flow inside a straight pipe (see Schmid & Henningson (1994) and citations therein).…”
Section: Stability Analysissupporting
confidence: 92%
“…However, as indicated by Kühnen et al (2015) and as will be shown herein, these results should be considered inaccurate, with the exception of the symmetry characteristics observed in the flow. The only experiments employing toroidal pipes are those by Kühnen et al (2014Kühnen et al ( , 2015. These authors sacrificed the 2π (streamwise) periodicity and the mirror symmetry of the system by introducing a steel sphere in the tube to drive the fluid.…”
mentioning
confidence: 99%
“…Comparing the calculated critical Reynolds numbers with the experimentally measured ones (Gelfgat, 2019), we obtained a good agreement with the recent experiments of Kühnen et al (2014Kühnen et al ( , 2015 done for < 0.1 and < 0.05. Several earlier experiments that studied the instability onset for similar pipe curvatures and small torsions (White, 1929;Taylor, 1929;Sreenivasan & Strykowski, 1983;Webster & Humphrey, 1993) found noticeably larger critical it can be estimated to be above 8000.…”
Section: Numerical Technique and Test Calculationssupporting
confidence: 88%
“…Transition to turbulence is subcritical at low curvatures and qualitatively similar to the one in straight pipes [30][31][32]. For larger δ, instead, transition is initiated by a supercritical Hopf bifurcation [30,[32][33][34] and all elements point towards a bifurcation cascade [33]. The dynamics of the flow at intermediate curvatures, however, remains largely unexplored, leaving unanswered the question of whether the two transition scenarios interact, and if so how.…”
mentioning
confidence: 97%
“…[30] but "could not be pinpointed" experimentally (quotations from Refs. [30,33]). Second, we move our attention to the region of the parameter space where the neutral curve of the flow intersects the threshold for subcritical transition [38], hereafter referred to as critical point, see Fig.…”
mentioning
confidence: 99%